Alteraciones audiovestibulares de lenguaje y foniátricas en microdeleción 22q11.2. - Barradas Hernández, María Isabel; Lino González, Ana Luisa (Anales de Otorrinolaringología Mexicana)
BACKGROUND: 22q11.2 deletion syndrome is a genetic disorder caused by a hemizygous microdeletion of the long arm of chromosome 22; its worldwide prevalence is 1 in every 2000 to 4000 live births. According to the literature, these patients may present, among other alterations: cardiac malformations, facial dysmorphism, developmental delay, intellectual disability, learning problems, velopharyngeal insufficiency, recurrent otitis, hearing loss and orthopedic abnormalities, so the treatment is usually multidisciplinary according to the clinical manifestations. CLINICAL CASE: A female patient, in which bilateral superficial hearing loss curves with a conductive pattern in the left ear, inadequate pressure management in both ears, left vestibular hypofunction, velopharyngeal insufficiency, delayed language development, and a learning disorder were found. CONCLUSIONS: Early and timely detection of this syndrome, as well as of the different alterations or disorders and the appropriate specialized multidisciplinary management, contribute to a better quality of life and reduce the impact of the different disabilities that may occur.